Digital Shopper's Dilemma: The Role of Lifestyle, Flash Sale, and Online Reviews in Repurchase Intentions - Arifin, Samsul; Roosdhani, Mohamad Rifqy; Komaryatin, Nurul; Ali, Ali; Huda, Nurul (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
The growth of the Muslim fashion industry, particularly the hijab among Muslim women many of whom can be found in Jepara, particularly at the Lovable Hijab Shop on Shopee is the driving force for this study. The purpose of this study is to ascertain how lifestyle, flash deals, and online reviews affect consumers' intentions to repurchase. (Study of Lovable Hijab Customers at Shopee). The population in this research are Lovable Hijab customers at Shopee who took part in the Flash Sale program. The sample used in the research was 99 respondents taken using the Slovin formula. The sampling technique uses the Random Sampling method (chosen at random), namely Lovable Hijab customers at Shopee who take part in the Flash Sale program. The independent variables of this research are lifestyle (X1), Flash Sale (X2), and Online Review (X3) as well as the dependent variable Repurchase Intention (Y). The results of this research show that the variables Life Style, Flash Sale, and Online Review have a positive influence on Repurchase Intention for Lovable Hijab on Shopee. The coefficient of determination value is 0.412. This shows that 41.2% of the factors influencing Repurchase Intention can be determined by lifestyle, Flash Sale, and Online Review. Meanwhile, factors not included in this study account for the remaining 58.8%.